PENGARUH PENDIDIKAN & PELATIHAN, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA FRONTLINER - Tri Irfa Indrayani, Tri Irfa Indrayani; Revi Erda, Revi Erda (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2018)
This study aims to reveal the effect of education and training, compensation and work discipline on Front liner performance at PT Bank Negara Indonesia (Persero), Tbk, Padang Branch. The method used is a quantitative method with multiple linear analysis. The population in the study was 89 Front liners. The sampling technique is total sampling. Data collection method by distributing questionnaires. To prove the hypothesis, t test and F test are used. The results of this study show that education and training, compensation, and work discipline have a positive and significant effect on the Front liner Performance of PT Bank Negara Indonesia Padang Branch. Partially it turns out that work discipline is the most dominant variable affecting Front liner performance of PT Bank Negara Indonesia Padang Branch. From the results of this study it is suggested that Education &Training (Training), Compensation and Work Discipline have been achieved partially and simultaneously which are relatively good to be maintained and even improved so that the Front liner's performance is increasing.